2023
DOI: 10.3389/fvets.2023.1114798
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the treatment of meningoencephalomyelitis of unknown origin since 2009: A review of 671 cases

Abstract: “Meningoencephalomyelitis of unknown origin” (MUO)—a collective term for a group of clinically-indistinguishable (but pathologically distinct) autoimmune diseases of the CNS—has become increasingly commonly recognized throughout the world. In the 1960s−1980s the focus was primarily on the pathological description of these conditions and, largely anecdotally, their response to glucocorticoids. The subsequent availability of magnetic resonance imaging for companion animals led to a focus on imaging characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 110 publications
1
25
2
Order By: Relevance
“…Nonetheless, despite the long study period, there is still no clear evidence of superiority of any specific treatment regimen with multicenter randomized controlled trials required to determine the superiority of a specific treatment. 23 We showed that pugs, the presence of seizures and paresis at the time of presentation, and a higher NDS score were associated with an increased risk of death at 6 months after diagnosis in dogs with MUO.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Nonetheless, despite the long study period, there is still no clear evidence of superiority of any specific treatment regimen with multicenter randomized controlled trials required to determine the superiority of a specific treatment. 23 We showed that pugs, the presence of seizures and paresis at the time of presentation, and a higher NDS score were associated with an increased risk of death at 6 months after diagnosis in dogs with MUO.…”
Section: Discussionmentioning
confidence: 71%
“…The presence of motor symptoms at onset of disease has been associated with unfavorable outcome in patients with multiple sclerosis (MS) [18][19][20][21][22] and several similarities between MS and MUO have been suggested recently. [23][24][25] It has been suggested that motor symptoms reflect either more extensive or more persistent functional effects or lesions. 26 Interestingly, no association was found between specific neurolocalizations (such as brainstem) and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Prednisolone in combination with other immunosuppressive medication has been reported to improve survival times, 3,27 although there is conflicting evidence to support this and more recent reviews have indicated favourable outcomes with glucocorticoids alone. 28 In our patient, prednisolone therapy was initiated early in the course of treatment; however, due to deterioration of the clinical signs, a second immunosuppressive drug (cytarabine) was administered. Different protocols have been described for cytarabine treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the knowledge gained is not easily applicable for clinical use, and need for establishment of robust clinical scores for evaluation of treatment has been suggested. [12]. Several established scales have been used to describe the neurological status of dogs, however its usefulness in prognostication was not been compared so far.…”
Section: Introductionmentioning
confidence: 99%